PENGEMBANGAN PERANGKAT PEMBELAJARAN DENGAN MODEL EXPERIENTIAL LEARNING PADA MATERI KUBUS DAN BALOK KELAS VIII SMP - Sari, Anita; Suanto, Elfis; Suhermi, Suhermi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack : The background of this research is the limited of learning device as a means of supporting learning referring to 2013 curriculum. This research aims to develop syllabus, Learning Implementation Plan (LIP) and Student Learning Worksheet (SLW) with experiential learning model on the subject of cubes and beams for 8th grade students of junior high school. The research used Research and Develomant (R&D) with the ADDIE procedure; analyze, design, development, implementation, and evaluation. Due to time constraints, this research is only done until the development stage. The research instrument used are sheet of learning device validation, questionnaire response of learnears and evaluation of learning outcomes. Syllabus, RPP and LKPD validated 2 times by 3 validators and revised according to the suggestion from the validator. The valid LKPD was then limited tested with the subject of nine students of 8th grade in SMP Muhammadiyah 1 Pekanbaru, Riau. Based on the analysis result of the validation data, it can be concluded that syllabus and RPP are considered very valid and LKPD is valid with average rating for syllabus is 3,44, RPP is 3,34 and LKPD is 3,13. In the second validation it can be concluded that the syllabus, RPP and LKPD are considered very valid with the average rating for the syllabus is 3.75, for the RPP is 3.65 and for LKPD is 3.47. Based on the analysis results of the questionnaire response of learners to LKPD in the limited trial is 95.5% with very practical category and the average of the result of student’s evaluation is 84.8. Based on the results of data analysis and discussion concluded that the syllabus, RPP and LKPD with experential learning model on the subject of cubes and beams for 8th grade students of Junior High School have fulfilled the validity and practical requirements to used by 8th grade students of Junior High School.Key Words : Experiential Learning Model, Learning Device, Cubes and Beams, Validity andPracticality